Biomolecular Interaction Studies Between Cytochrome PpcA From Geobacter sulfurreducens and the Electron Acceptor Ferric Nitrilotriacetate (Fe-NTA) - Ferreira, Marisa R.; Salgueiro, Carlos A. (Frontiers in Microbiology, 2018)
Geobacter sulfurreducens is a dissimilatory metal-reducing bacterium that exhibits an enormous respiratory versatility, including the utilization of several toxic and radioactive metals as electron acceptors. This versatility is also replicated in the capability of the most abundant cytochrome in G. sulfurreducens, the periplasmic triheme cytochrome PpcA, to reduce uranium, chromium and other metal ions. From all possible electron transfer pathways in G. sulfurreducens, those involved in the iron reduction are the best characterized to date. In a previous work we provided structural evidence for the complex interface established between PpcA and the electron acceptor Fe(III)-citrate. However, genetic studies suggested that this acceptor is mainly reduced by outer membrane cytochomes. In the present work, we used UV-visible measurements to demonstrate that PpcA is able to directly reduce the electron acceptor ferric nitrilotriacetic acid (Fe-NTA), a more outer membrane permeable iron chelated form. In addition, the molecular interactions between PpcA and Fe-NTA were probed by Nuclear Magnetic Resonance (NMR) spectroscopy. The NMR spectra obtained for natural abundance and 15N-enriched PpcA samples in the absence and presence of Fe-NTA showed that the interaction is reversible and encompasses a positively charged surface region located in the vicinity of the heme IV. Overall, the study provides for the first time a clear illustration of the formation of an electron transfer complex between PpcA and a readily outer-membrane permeable iron chelated form. The structural and functional relationships obtained explain how a single cytochrome is designed to effectively interact with a wide range of G. sulfurreducens electron acceptors, a feature that can be explored for optimal bioelectrochemical applications.